Learning of Addition and Subtraction Operations - Situmorang, Naila Izzatul Fikriyah; Az-Zahra, Zafira; Erli, Ika Sucinta; Fitriani, Viona; Maulana, Adam; Harianja, Chorry Novita; Balqis, Ratu; Mulyani, Siti; Hapiza, Asra; Nurhaswinda, Nurhaswinda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The purpose of this study is to describe how the learning process of addition and subtraction operations is carried out. The object of this research is the learning of addition and subtraction operations, while the subjects are elementary school students. In this study, data collection was carried out by searching for journal references through online media such as Google Scholar. Addition and subtraction operations are fundamental parts of mathematics, usually taught at the early levels of elementary school. These operations are often introduced using concrete objects or pictures to make them easier for children to understand. Addition is understood as the process of combining two groups of objects, while subtraction is seen as the process of taking away a part of a group. This research was conducted through literature study using data analysis techniques. The use of concrete media and conceptual approaches has been proven effective in improving students’ understanding. Therefore, teachers need to choose appropriate learning strategies so that the material can be optimally understood by students.